Hybrid Solar/Heat Pipe/Thermoelectric Power Generation - Lee, Jie Sheng (2015)
Solar energy is a renewable heat source freely and widely available everywhere in Malaysia throughout the year. Heat pipes are passive and very efficient heat transfer devices. Thermoelectric devices can be used for thermoelectric power generation from waste heat. A hybrid system with a combination of heat pipe solar collector and thermoelectric could provide both power and hot water simultaneously. An experimental set up was established that consisted of an evacuated glass tube heat pipe solar collector, four thermoelectric modules and four water cooling jackets. Investigations were conducted under outdoor conditions in order to determine and evaluate the performance of such a hybrid system. Typical daily experimental results showed that all temperatures and DC output voltage increased as the day progressed and peaked to their maximum values around 15.30 hour and then started to decrease. On a sunny day with very little cloud cover, at the peak around 15.15 hour, the system was able to generate 0.114 W of power albeit at a very low electrical efficiency of only about 0.15 %. Recommendations for future studies are presented in the hope to achieve better results.